The Efficacy of Hands on Workshop on Infection Control to Healthcare Professionals: An Intervention Study - Mukry, Samina Naz; Safdar, Dilnasheen; Ali, Riafat; Attari, Ashfaq Ahmed; Shamsi, Tahir Sultan (LIAQUAT MEDICAL RESEARCH JOURNAL, 2021)
Strict compliance with basic infection control practices such as standard precautions is a simplest way of controlling spread of hospital acquired infections. A one day hands on infection control workshop was conducted at National Institute of Blood Diseases in April 2017. The nursing staff (NS; n=51) and allied healthcare professionals (AHCP; n= 24) at the institute were requested to participate in this study. The participants were informed verbally and asked to fill out a short questionnaire right before starting and at the end of the workshop to evaluate their knowledge and performance/attitude towards general infection control practices. The response rate, mean and standard deviation of each test score were determined using SPSS version 23. There was a significant difference between the pre-workshop and post-workshop test scores for nurses (p=0.0000005).The score for AHCP was comparatively better than the nurses in pre-workshop test with an average of 11.25±1.11. Although the result for the AHCP improved in post-workshop but difference between the mean scores was statistically insignificant (p=1). Gaps in knowledge and attitude/ performance were observed based on percentage of right answers in both categories but a significant difference p=0.0042 was observed in performance and attitude category in post workshop test scores. It can be concluded that educational session along with hands on workshops can be a significant tool in building a culture of safety environment in a hospital.